Antimicrobial prescription pattern in the Deido health district, Douala, Cameroon - Charles Njumkeng; Elvis T Amin; Prudence Tatiana Nti Mvilongo; Denis Zofou; Jane Francis KT Akoachere; Patrick A Njukeng (Archives of Community Medicine and Public Health - Peertechz Publications, 2023)
Inappropriate antimicrobial prescriptions are among the highest contributing factors to Antimicrobial Resistance (AMR). Most low and middle-income (LMICS) countries with high AMR burdens like Cameroon, seldom document information on prescription patterns, whereas this information is crucial in addressing inappropriate antimicrobial prescriptions. This study was therefore designed to elucidate antimicrobial prescription patterns in order to tailor interventions to mitigate AMR in Cameroon. The study adopted a multicentre cross-sectional design. Information on antimicrobial prescriptions was collected from four hospitals within the Deido Health District, between October 2019 and March 2020. Of the 1398 participants that were enrolled in the study, the most presented age group were participants aged 15-45 years 913(65.3%) and prescriptions were higher amongst females (923,53.6%). The highest number of antimicrobial prescriptions was made in the outpatient department 592(42.3%) followed by the pediatric unit, 344(24.6%). Most of the prescriptions were for patients with respiratory tract infections 436 (31.2%), followed by those with digestive tract infections 248 (17.7%). The most frequently prescribed class of drugs were the Penicillins 690 (40.3%, 37.8 - 42.6), with Amoxicillin clavulanic acid accounting for 27.8% of the overall prescriptions followed by Cephalosporins 392 (22.7, 20.6 - 24.7), with Ceftriaxone being the most prescribed in the class (13.3%). The need for prescription was mainly determined by clinical judgement (61.1%), while only 9.5% of prescriptions were based on antimicrobial sensitivity test. In the struggle to mitigate AMR, there is a great need to exploit data on prescription patterns and develop stewardship programs in order to optimise antimicrobial use in Cameroon. We emphasize in this communication the potential benefits and outcomes of foresight thinking, such as improved resilience, better resource allocation, and effective response strategies.